Internet of things based humidity control and monitoring system - Eka Purnama Harahap; Md Asri Ngadi; Untung Rahardja; Faisal Rizki Azhari; Kenita Zelina (ILKOM Jurnal Ilmiah, 2021)
This study proposes smart monitoring by utilizing IoT in agriculture which aims to assist farmers in monitoring crops in order to reduce the risk of failure. Quantitative method was employed to collect data from the Soil Moisture Sensor and DHT22 which are to read and write data that can be monitored on a cloud server or csv file to evaluate the risk. This monitoring system is created using the Python programming language by utilizing the Raspberry Pi as a microprocessor. The result of this study is data acquisition that is connected to the internet. Data can be accessed at Thingspeak to show indications and crop yields. Analogue form and indicators of water in soil moisture are indicated by colored marks. Proper monitoring shows more accurate crop data that enable the farmers to prevent crops from drying out. This system is expected to reduce the risk of crop failure as well as increase the agriculture productivity.